Aerosol Generation During Nasal Airway Instrumentation. (28th January 2023) - Sayahi, Tofigh; Workman, Alan D.; Kelly, Kerry E.; Ardon‐Dryer, Karin; Presto, Albert A.; Bleier, Benjamin S.
Abstract: Objective: Airborne aerosol transmission, an established mechanism of SARS‐CoV‐2 spread, has been successfully mitigated in the health care setting through the adoption of universal masking. Upper airway endoscopy, however, requires direct access to the face, thereby potentially exposing the clinic environment to infectious particles. This study quantifies aerosol production during rigid nasal endoscopy (RNE) and RNE with debridement (RNED) as compared with intubation, a posited gold standard aerosol‐generating procedure. Study Design: Prospective cross‐sectional study. Setting: Subspecialty single‐center clinic and surgical study. Method: Three aerosol detectors (NANOSCAN‐3910, OPS‐3330, and APS‐3321) with a particle size sensitivity of 10 to 20, 000 nm were utilized to detect particulate production during the clinical care of 209 patients undergoing RNE/RNED and 25 patients undergoing intubation. Results: RNE and RNED produced statistically significant particles over baseline in 29.3% and 51.0% of subjects ( P = .003‐.049 and .002‐.047, respectively). Intubation produced statistically significant particles in 31.2% ( P = .001‐.015). The mean ± SD particle diameter in all tests was 69.9 ± 10.5 nm with 99.7% <300 nm. There were no statistical differences in particle production among RNE, RNED, and intubation. The presence of concomitant cough, sneeze, or prolonged speech similarly did not significantly affect particle production during any procedure. Conclusions: Instrumentation of nasal airway produces airborne aerosols to a similar degree of those seen during intubation, independent of reactive patient behaviors such as cough or sneeze. These data suggest that an improved understanding is necessary of both the definition of an aerosol‐generating procedure and the functional consequences of procedural aerosol generation in clinical settings.